2008
DOI: 10.1103/physrevc.78.054609
|View full text |Cite
|
Sign up to set email alerts
|

Angular momentum dependence of the nuclear level-density parameter aroundZ~50

Abstract: α-particle evaporation spectra and γ -ray multiplicities were measured for various target-projectile systems corresponding to residual nuclei in the range of Z R = 48-55 and with excitation energy in the range of 30-40 MeV. The high-energy part of the evaporation spectra were analyzed using the statistical model code PACE2 to derive values of the inverse level-density parameter (K). The K values were found to be in the range of 9.0-10.5 for all systems. Angular momentum dependence of the inverse level-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A systematic reduction of k with increasing <J> in the range of ≈10 -20 have been reported in the recent neutron evaporation studies around A ≈ 90 -120 [38][39][40]. On the other hand, angular momentum gated α-particle evaporation measurement around A ≈120, and J ≈10 -20 showed complex variation of k with angular momentum [37]. In contrast to the strong dependence of the LD parameter on the angular momentum reported in the above mentioned works, experimental data for the heavier systems showed less sensitivity of k on J [35,36].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…A systematic reduction of k with increasing <J> in the range of ≈10 -20 have been reported in the recent neutron evaporation studies around A ≈ 90 -120 [38][39][40]. On the other hand, angular momentum gated α-particle evaporation measurement around A ≈120, and J ≈10 -20 showed complex variation of k with angular momentum [37]. In contrast to the strong dependence of the LD parameter on the angular momentum reported in the above mentioned works, experimental data for the heavier systems showed less sensitivity of k on J [35,36].…”
Section: Introductionmentioning
confidence: 83%
“…In the level density formulations based on the simplistic FGM, the level density parameter does not explicitly depend on the excitation energy or angular momentum. However, a number of earlier studies have shown that the parameter k (and thus a) depends on excitation energy (temperature) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34], and angular momentum [35][36][37][38][39][40][41][42] both, in an intricate manner. Such departures from the FGM may not be surprising as the actual single-particle spectrum of a nucleus is considerably complicated than the simple Fermi gas picture.…”
Section: Introductionmentioning
confidence: 99%
“…In one of these experiments with A~ 180, E *~ 56-59 MeV, and <J> ~15-30 ħ, the inverse level density parameter k was found to remain constant within the statistical errors in the measured angular momentum range [2]. In the other experiment performed at A ~120, E * ~ 60 MeV and J ~ 10-20 ħ, no systematic variation of inverse level density parameter was observed [3]. For Z R = 49, 50, and 51 (Z R is the atomic number of the evaporation residue) k was found to be constant while for the other cases it was observed to increase with increasing angular momentum.…”
Section: Introductionmentioning
confidence: 84%
“…In recent years a number of studies have been carried out to understand the angular momentum (J) dependence of nuclear level density both theoretically and experimentally. In a couple of recent experiments [2,3], angular momentum dependences of NLD were studied by analyzing the α-particle evaporation spectra emitted from various compound systems. In one of these experiments with A~ 180, E *~ 56-59 MeV, and <J> ~15-30 ħ, the inverse level density parameter k was found to remain constant within the statistical errors in the measured angular momentum range [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is now a well-known fact that the density of quantum mechanical states increase rapidly with excitation energy and the nucleus shifts from discreteness to quasi-continuum and continuum where the statistical concepts, in particular, the nuclear level density (NLD) [1,2,3,4,5] which is the number of excited levels around an excitation energy, are crucial for the prediction of various nuclear phenomena, astrophysics [6] and nuclear technology. Recent measurements of the evaporation spectra of particles emitted from the highly excited compound nuclear systems in a hot and rotating state have provided [7,8,9,10,21] some information to understand the interdependence between the nuclear level density (NLD) and the key parameters such as excitation energy, isospin and most importantly the angular momentum, collective and non-collective excitations. The NLD parameter related to the density of the single particle levels near the Fermi surface is influenced by the shell structure and the shape of the nucleus which in turn are profoundly altered by the excitations [11,12,13,14,15,16,17,18].…”
mentioning
confidence: 99%